Factors Affecting Knowledge of Mothers Toward Complete Basic Immunization in Jakarta - Bunga Romadhona Haque; Ulfah Septa Arseda (STIKep PPNI Jawa Barat, 2022)
Aims : This study aimed to determine factors affecting knowledge of mothers toward complete basic immunization. Design: This research is analytic with a cross-sectional approach Methods: This research method used a cross-sectional approach. The samples in this study were 20 mothers at the Melati Asih Posyandu in 2020. Results : It was found that the variables of knowledge, education and sources of information, had a significant relationship with the accuracy of the basic immunization schedule (p<0.05), while the work and experience variables did not have a significant relationship with the accuracy of the basic immunization schedule. Conclusions : Therewas a significant relationship between knowledge, education, sources of information and the accuracy of the basic immunization schedule.